2010
DOI: 10.1007/s00705-010-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

First molecular detection of Aichi virus in sewage and shellfish samples in the Monastir region of Tunisia

Abstract: The aims of our investigations were (1) to look for Aichi virus in environmental samples and (2) to compare the Aichi virus strains in both clinical and environmental samples in order to evaluate the role of environmental contamination as a possible vehicle for viral transmission. Aichi virus was detected in 15 (6%) sewage samples and in 4 (6.6%) shellfish samples. Aichi virus was identified for the first time in water samples. Phylogenetic analysis revealed several clusters that occurred sequentially in time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 18 publications
5
39
0
Order By: Relevance
“…A total of 260 distinct AiV strains were identified from wastewater and river water samples, with a considerable genetic diversity ( Fig. 1 and 2), which was much larger than the number of AiV strains identified in any other previous environmental studies (1,22). Among the strains identified, 255 were classified into genotype A and 5 were genotype B.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…A total of 260 distinct AiV strains were identified from wastewater and river water samples, with a considerable genetic diversity ( Fig. 1 and 2), which was much larger than the number of AiV strains identified in any other previous environmental studies (1,22). Among the strains identified, 255 were classified into genotype A and 5 were genotype B.…”
mentioning
confidence: 86%
“…Fecal-oral AiV transmission through contaminated food or water is indicated by AiV detection in fecal samples of infected individuals (2, 7, 12-17, 19, 20, 23, 27) and raw and treated sewage (22), sewage-polluted river water (1), and shellfish samples (4,12,22). To further elucidate their prevalence and infection route, comprehensive documentation of their environmental occurrence and fate is essential.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since its discovery, AiV has been detected with an incidence of 0.9–4.1%, primarily when studying outbreaks of diarrhea in children or young adults [14-18]. AiV seems to be circulating worldwide, and detection of AiV has been reported in Asia [19], South America [20], Europe [13-15, 20], and Africa [17]. Previous studies have suggested oysters, or other seafood, to be the source of AiV infections [2, 14, 17, 21, 22] but its occurrence has also been reported in sewage [17, 23], which indicates that kobuviruses might use the fecal-oral route of infection, like several other picornaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…AiV seems to be circulating worldwide, and detection of AiV has been reported in Asia [19], South America [20], Europe [13-15, 20], and Africa [17]. Previous studies have suggested oysters, or other seafood, to be the source of AiV infections [2, 14, 17, 21, 22] but its occurrence has also been reported in sewage [17, 23], which indicates that kobuviruses might use the fecal-oral route of infection, like several other picornaviruses. Although doubts exist regarding its clinical role because of frequent codetection (50–80%) of AiV and other viral agents [14, 15, 24] and low incidence rates (0.9–4.1%) in acute gastroenteritis [15, 24-26], other studies have recently yielded contrasting results, showing that codetection of AiV with other common enteropathogenic viruses occurs at a low rate [27] and that this virus is rarely detected in healthy individuals [27-29], which supports a possible role of this virus in gastroenteritis.…”
Section: Introductionmentioning
confidence: 99%